Tinjauan Yuridis Perjanjian Kerjasama Dalam Layanan Jasa Kontraktor Antara PT. Permata Karya Lombok Dengan PT. Jaya Raharja - Abdul Jihad; Eka Jaya Subadi (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the implementation procedures and the parties' responsibilities in the event of a breach of contract in the contracting service cooperation agreement between PT.Permata Karya Lombok and PT.Jaya Raharja. This study uses empirical normative legal research. The study results indicate that (1) the procedure for implementing the cooperation agreement is based on the principle of freedom of contract. It means that both parties are free to determine the agreement's contents without interference from other parties. It is not prohibited by law.(2) The parties' responsibility in the event of a breach of contract is the settlement by negotiation or bargaining concerning the interests of dispute resolution to reach an agreement.